Harry Potter Revisited: Normativity and LGBT Experiences - López Pascual, Helena (Journal of Artistic Creation and Literary Research, 2025)
Between 1997 and 2007, British author J. K. Rowling published seven books that caused a revolution in children’s literature and immortalized their protagonist, Harry Potter, as one of the main icons of this century’s popular culture. The Harry Potter series have sold millions of copies, have been translated to eighty languages and taken to the big screen by Directors such as Alfonso Cuarón or David Yates. This project aims to revisit this famous saga and to analyze it from a critical perspective, focusing on the queer experiences that can be drawn from an in-depth reading of the books. The plot of the novels is based on a subversion of socially established normativity, and therefore the projection of queer experiences on the characters is not difficult to imagine. The character of Dumbledore will be closely scrutinized on his own, for he is the only confirmed homosexual character in the Potter universe; however, the way his sexuality is addressed —or, rather, not addressed— actually ends up consolidating heteronormativity. Along those lines, it will be explored how stereotypes in children’s literature bear the potential to harm readers’ upbringing and self-image. Finally, it will be commented how LGBT readers of these books may project their own experiences through fanfiction and online forums, in an attempt to both counterbalance the shortage of representation in the canonical works and to explore their sense of self.